Regional crustal-scale structural control on epithermal deposits within the Hauraki Goldfield, Coromandel Volcanic Zone, New Zealand: insight from integrated geological and aeromagnetic structural patterns. Issue 4 (2nd October 2019) - Bahiru, Engdawork A.; Rowland, Julie V.; Eccles, Jennifer D.; Kellett, Richard L.
ABSTRACT: The Hauraki Goldfield of the Coromandel Volcanic Zone (CVZ) hosts up to 50 adularia-sericite epithermal Au-Ag deposits that young towards the southeast and align within NNE-to-NE trending structural corridors. We jointly interpret regional aeromagnetic data and a compilation of available geological data to identify structures that have influenced mineralisation. Systematic processing of aeromagnetic data and 'worming' edge detection provides a means of linking deep-seated aeromagnetic patterns with surface geology. The > 80 km long NNW-trending Whangamata-Coromandel lineament that persists to > 3 km depth and the NW-SE-trending Martha-Thames lineament are spatially linked to zones of hydrothermal alteration and epithermal deposits. Similar correlations are seen with deeply sourced NNE-trending lineaments contiguous with shallow sourced anomalies here interpreted as fault-angle basins. Our results are consistent with a model in which inherited basement fabrics appear to have influenced the late Miocene-to-Present tectonic segmentation of the CVZ, with implications for the localisation of epithermal mineralisation.